Development of Comorbid Depression after Social Fear Conditioning in Mice and Its Effects on Brain Sphingolipid Metabolism - Zoicas, Iulia; Mühle, Christiane; Schumacher, Fabian; Kleuser, Burkhard; Kornhuber, Johannes (Cells, 2023)
Currently, there are no animal models for studying both specific social fear and social fear with comorbidities. Here, we investigated whether social fear conditioning (SFC), an animal model with face, predictive and construct validity for social anxiety disorder (SAD), leads to the development of comorbidities at a later stage over the course of the disease and how this affects the brain sphingolipid metabolism. SFC altered both the emotional behavior and the brain sphingolipid metabolism in a time-point-dependent manner. While social fear was not accompanied by changes in non-social anxiety-like and depressive-like behavior for at least two to three weeks, a comorbid depressive-like behavior developed five weeks after SFC. These different pathologies were accompanied by different alterations in the brain sphingolipid metabolism. Specific social fear was accompanied by increased activity of ceramidases in the ventral hippocampus and ventral mesencephalon and by small changes in sphingolipid levels in the dorsal hippocampus. Social fear with comorbid depression, however, altered the activity of sphingomyelinases and ceramidases as well as the sphingolipid levels and sphingolipid ratios in most of the investigated brain regions. This suggests that changes in the brain sphingolipid metabolism might be related to the short- and long-term pathophysiology of SAD.
CRIS-Team Scopus Importer:2023-06-09
Keywords: acid ceramidase; acid sphingomyelinase; anxiety-like behavior; ceramide; depressive-like behavior; neutral ceramidase; neutral sphingomyelinase; social anxiety; sphingolipids; sphingomyelin